JENIS PUISI PENYAIR MUDA BANGKALAN DALAM KUMPULAN PUISI BERSAMA KELUARGA BESAR PENYAIR BANGKALAN - Yuliati, Ana (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2018)
Poetry is an expression of feeling from the experience of imagination, expressed in the form of kias in various types, according to the imagination of each poet. In this era, poetry is increasingly in demand by the public. In the past, poetry was probably only sought after by poets who had indeed been in literature for years. But nowadays, with the presence of Indonesian Language subjects in schools both at the Elementary School, First Level, Upper Level, to Higher Education and extracurricular activities in schools, so many students are interested in producing a work through writing poetry. By being embraced by a community or independent, they start working. The purpose of this study is to describe the types of poems contained in the Bangkalan Young Poet Collections of Poetry in accordance with the poetry classification. This research approach uses a qualitative descriptive approach. The data source of this research is the Collection of Poetry of the Bangkalan Poet Family, published by the Komunitas Masyarakat Lumpur, in 2017. The method of data collection and analysis used in this study is a descriptive method. Data collection techniques used are documentation techniques, while data analysis techniques use content analysis techniques. The findings of the data on the type of poetry of the young Bangkalan poet in the poetry collection of the Bangkalan Poet Family, the types of poetry used are new poetry and contemporary poetry. In the new poem, the type of poetry used is predominantly form-based poetry. Whereas in contemporary poetry, the type of poetry used is more dominant in word play, both repeated words and counter-words, besides typography is also used by young Bangkalan poets in an effort to strengthen poetry's meaning or sound through typography.